2014
DOI: 10.1158/1535-7163.mct-14-0027
|View full text |Cite
|
Sign up to set email alerts
|

Translational Exposure–Efficacy Modeling to Optimize the Dose and Schedule of Taxanes Combined with the Investigational Aurora A Kinase Inhibitor MLN8237 (Alisertib)

Abstract: Aurora A kinase orchestrates multiple key activities, allowing cells to transit successfully into and through mitosis. MLN8237 (alisertib) is a selective Aurora A inhibitor that is being evaluated as an anticancer agent in multiple solid tumors and heme-lymphatic malignancies. The antitumor activity of MLN8237 when combined with docetaxel or paclitaxel was evaluated in in vivo models of triple-negative breast cancer grown in immunocompromised mice. Additive and synergistic antitumor activity occurred at multip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 55 publications
1
42
0
Order By: Relevance
“…25 Others have found that the unique mitotic toxicity of alisertib may synergize with cytotoxic chemotherapy to enhance efficacy. 1518 Herein we report the results of a phase I study of alisertib combined with conventional induction chemotherapy for newly diagnosed AML.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Others have found that the unique mitotic toxicity of alisertib may synergize with cytotoxic chemotherapy to enhance efficacy. 1518 Herein we report the results of a phase I study of alisertib combined with conventional induction chemotherapy for newly diagnosed AML.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 This process appears especially applicable to cells during or shortly following exposure to cytotoxic chemotherapy. 1518 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, illumination of mRBCs conveying Cy5‐B12‐OH 2 has little or no effect on the integrity of the vasculature relative to that of mRBCs transporting Cy5‐B12‐TAX. Finally, we note that the maximum tolerated dose of docetaxel injected intravenously to mice is ≈250 µg per mouse (10 mg kg −1 ) . Typical dosage for treatment in mice is anywhere between 75 µg per mouse for low dosage up to the experimental maximum tolerated dose for high dosage .…”
Section: Resultsmentioning
confidence: 89%
“…Because pharmacological inhibition of Aurora kinase A overrides SAC-mediated mitotic arrest and aggravates chromosomal instability, the combination of anti-mitotic agents and Aurora kinase A inhibitor enhances chemosensitivity. Aurora kinase A inhibition by MK-5108 and alisertib increases the anti-tumor activity of docetaxel, paclitaxel, and vincristine [27, 48, 51, 6466], whereas Aurora A overexpression increases resistance to taxol [67]. Overall, targeting the mitotic functions of Aurora A using pharmacological inhibitors increases the anti-cancer effect of anti-mitotic agents.…”
Section: Discussionmentioning
confidence: 99%